Assessment of Business Environment of Women Involved in Micro, Small, and Medium Enterprises (MSMEs) in The Philippines: A Comparative Study with Select ASEAN Countries - Myrtle Faye Laberinto Solina (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2020)
The United Nations Conference on Trade and Development in 2017 states that women are deemed important part of a trade. They take part in a wide range of activities in the industry - produce products, commerce of goods across borders, run and own trading firms, and make up a large part of the workforce in export-oriented businesses. Nevertheless, women's potential and skills in trade is still too often held back by the many constraints. Hence, the research endeavours to describe the current demographics, roles, and experiences of women involved in MSMEs, provide information on the current policies programs and services and how these are comparable and contrasting, not to mention recommend measures to address the impeding factors in the Philippines to be compared with Singapore and Myanmar using available secondary information. Through surveys and purposive sampling, the research results show that women’s participation in economic activity, in particular in MSMEs, is primarily affected by conditions that catalyze engagements.